Being Christian in late antiquity: a festschrift for Gillian Clark - Harrison, Carol; Clark, Gillian (Oxford University Press, 2014)
What do we mean when we talk about 'being Christian' in late antiquity? This volume brings together 16 world-leading scholars of ancient Judaism, Christianity and Greco-Roman culture and society to explore this question, in honour of the ground-breaking scholarship of Professor Gillian Clark